Identity, accent aim, and motivation in second language users: New Scottish Gaelic speakers' use of phonetic variation. (April 2016) - Nance, Claire; McLeod, Wilson; O'Rourke, Bernadette; Dunmore, Stuart
Abstract : This paper examines the use of phonetic variation in word‐final rhotics among nineteen adult new speakers of Scottish Gaelic, i.e. speakers who did not acquire the language through intergenerational transmission. Our speakers learned Gaelic as adults and are now highly advanced users of the language. We consider variation in their rhotic productions compared to the productions of six older, traditional speakers. Previous approaches to variation in second language users have either focussed on how variable production will eventually result in native‐like 'target' forms (Type 1 study), or have investigated the extent to which second language users reproduce patterns of variation similar to 'native speakers' (Type 2 study). We additionally draw on sociocultural approaches to Second Language Acquisition and apply notions of accent aim, identity construction, and learning motivation in order to fully explore the data. In doing so, we advocate a 'Type 3' approach to variation in second language users.